Identifikasi Morfologi Aksesi Srikaya (Annona squamosa) di Gedangsari Gunungkidul - Danang Setiono; Parjanto Parjanto; Djati Waluyo Djoar (Universitas Sebelas Maret, 2013)
The purpose of this study to determine the morphological characteristics and variability of planting sugar apple Gedangsari, Gunungkidul, Yogyakarta. Identify the morphological characteristics conducted on 36 plant samples (36 accessions) based method on stratified sampling and purposive sampling. The data were analyzed descriptively and clustering analysis. The results of the research showed that sugar-apple had pyramida canopy shape, plant height of 264±525 cm, oblongus leaves type, integer leaves margins, acuminatus leaves tip form, base acutus leaves, petiole cylindrical shape, dark green petiole, dark green color of the upper surface leaves, faded green color of the lower surface, leaves length 16.06±8.23 cm, leaves width 3,73±6,9 cm, leaves area 24,28±85,71 cm2, round shaped of rod, patens branching pattern, stem circumference 17,5±38 cm, axillary flos of flower layout, having 3 petals, whitish green of flower color, is cordate and round shape of fruit, fruit weight of 83,03±180,3 g, fruit circumference 22,4±19,36 cm, flesh thick 1,73±3,66 mm, whitish green and green of fruit color, the total amount of fruit scales 70±104,66, and the value of PTT between 18-29 obrix, blunt shape of fruit scales, ellipsoid shape of seeds, number seeds 7±70,66 and total seed weight 2,3±19,86g. There were variability include leaves length, leaves width, leaves area, stem girth, fruit weight, fruit girth, fruit flesh thickness, number of fruit scales, PTT values and fruit shape and the fruit skin’s color. The result of clustering analysis showed that similarity coefficient between the accessions was 66%.